The identity of Pilumnus dofleini Balss, 1933 (Crustacea: Decapoda: Brachyura: Pilumnidae), with descriptions of three new species from the Western Pacific - Komai, Tomoyuki; Motoh, Hiroshi (Zootaxa, 2012)
The identity of the pilumnid crab, Pilumnus dofleini Balss, 1933, is reassessed based on the female holotype and additional male specimens from Sagami Bay and the Sea of Japan, Japan. Three new species allied to P. dofleini are described and illustrated: P. curvipenis n. sp. from the Izu Islands, Japan; and P. armatus n. sp. and P. bohol n. sp. from the Bohol Sea, the Philippines. These four species are diagnosed, compared and differentiated from the related P. acanthosoma Ng, 2000.